A low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and preparation method thereof
By using low dielectric flame-retardant additive film with optimized distribution ratios such as negatively charged core-shell rubber particles in the FCBGA packaging loading plate, the existing additive film has solved the problems of large thermal expansion coefficient, poor dielectric performance, poor flame-retardant performance and poor mechanical performance in the FCBGA packaging loading plate, and the low thermal expansion coefficient, low dielectric loss, good flame-retardant performance and high mechanical performance of the additive film are achieved.
Patent Information
- Application Number
- CN202310209334.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The existing reinforcement films have problems such as large thermal expansion coefficient, poor dielectric performance, poor flame retardant performance and poor mechanical performance in the FCBGA packaging loading plate.
A low-dielectric flame-retardant layered adhesive film including negatively charged core-shell rubber particles, epoxy resin, inorganic filler, phenoxy resin, phenolic resin, maleimide and benzoxazine is used. Through the reasonable proportioning and treatment of these components, the thermal expansion coefficient is reduced, the dielectric and flame retardant properties are improved, and the mechanical properties are enhanced.
The low thermal expansion coefficient, low dielectric loss, good flame retardant performance and high mechanical properties of the additive film are achieved, meeting the application needs of FCBGA packaging load board.
Smart Images

Figure CN116042157B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin composite materials, and in particular to a low-dielectric flame-retardant build-up layer adhesive film for an FCBGA package carrier and a preparation method thereof. Background Art
[0002] The flip chip ball grid array (FC-BGA) substrate is a high-density packaging substrate that can achieve high-speed and multifunctional chips. Based on the difficulty of manufacturing semiconductor packaging substrates, market size, and development trends, packaging substrates are mainly divided into three categories: entry-level, general, and high-end, among which FC-BGA packaging substrates belong to the high-end category. FCBGA substrates are basically made using the more sophisticated semi-additive method (SAP for short). In the SAP process, a build-up film must be used, so it becomes the core key material in FCBGA substrates.
[0003] However, the existing build-up film has obvious thermal expansion phenomenon, which can easily lead to obvious deformation of the film after curing; at the same time, the dielectric properties are poor, and dielectric loss is easy to occur under the action of alternating electromagnetic fields; in addition, the flame retardant properties of the build-up film need to be improved to ensure reliability in use under high temperatures; and the existing build-up film has poor mechanical properties, and the bonding strength between it and the copper formed by the semi-additive method needs to be improved.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof, aiming to solve the problems of large thermal expansion coefficient and poor dielectric performance of the existing build-up adhesive film.
[0006] The technical solution of the present invention is as follows:
[0007] A low-dielectric flame-retardant build-up layer adhesive film for an FCBGA package carrier comprises, by weight: 5-10 parts of negatively charged core-shell rubber particles, 15-30 parts of epoxy resin, 50-100 parts of inorganic filler, 10-20 parts of phenoxy resin, 2-5 parts of phenolic resin, 10-45 parts of maleimide and 10-20 parts of benzoxazine.
[0008] The low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier, wherein the negatively charged core-shell rubber particles are obtained by immersing the core-shell rubber particles in a negatively charged impregnation liquid and then undergoing a vacuum baking treatment; the immersion conditions are: the immersion temperature is 20-30°C, the relative humidity is 40-60%, and the immersion time is 1-2h; the vacuum baking conditions are: the vacuum baking temperature is 60-80°C, and the vacuum baking time is 1-2h.
[0009] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the maleimide is selected from one or more of phenol-containing bismaleimide, diphenylmethane bismaleimide, diaminobenzene bismaleimide, diaminodiphenylmethane bismaleimide, and polycyclic modified maleimide.
[0010] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the polycyclic modified maleimide is selected from one or more of polycyclic modified maleimide I, polycyclic modified maleimide II, and polycyclic modified maleimide III;
[0011] Wherein, the structural formula of the polycyclic modified maleimide I is
[0012] The structural formula of the polycyclic modified maleimide II is
[0013] The structural formula of the polycyclic modified maleimide III is
[0014] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the benzoxazine is selected from one or more of bisphenol A type polybenzoxazine, naphthol type polybenzoxazine, unsaturated bond-containing polybenzoxazine, diamine type polybenzoxazine, and DOPO-containing benzoxazine.
[0015] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the benzoxazine containing DOPO is selected from one or more of benzoxazine I containing DOPO, benzoxazine II containing DOPO, benzoxazine III containing DOPO, and benzoxazine IV containing DOPO;
[0016] Wherein, the structural formula of the DOPO-containing benzoxazine I is
[0017] The structural formula of the DOPO-containing benzoxazine II is
[0018] The structural formula of the DOPO-containing benzoxazine III is
[0019] The structural formula of the DOPO-containing benzoxazine IV is
[0020] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the epoxy resin is selected from one or more of bisphenol epoxy resin, biphenyl epoxy resin, phenol epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin and naphthol phenolic epoxy resin;
[0021] The inorganic filler is selected from one or more of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, and zirconium phosphate;
[0022] The phenolic resin is selected from one or more of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin and dicyclopentadiene phenolic resin.
[0023] The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, wherein the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier, in parts by weight, further comprises: 0.1-0.5 parts of curing accelerator, 3-9 parts of other additives, and 200-300 parts of organic solvent;
[0024] Wherein, the curing accelerator is selected from one or more of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, 4-dimethylaminopyridine, and 2-phenylimidazole;
[0025] The other auxiliary agents are selected from one or more of thickeners, defoamers, leveling agents, leveling agents, adhesion-imparting agents, and colorants;
[0026] The organic solvent is selected from one or more of toluene, xylene, butanone, methyl ethyl ketone, cyclohexanone, ethyl acetate, and N,N-methylformamide.
[0027] The low-dielectric flame-retardant build-up layer adhesive film for the FCBGA package carrier has a thickness of 10-100 μm.
[0028] A method for preparing a low-dielectric flame-retardant build-up layer adhesive film for a FCBGA package carrier comprises the following steps:
[0029] providing a substrate;
[0030] The components of the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier are mixed in parts by weight, coated on the substrate, and dried to obtain the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier.
[0031] Beneficial effect: The present invention provides a low-dielectric flame-retardant build-up layer adhesive film for FCBGA packaging carrier and a preparation method thereof. The low-dielectric flame-retardant build-up layer adhesive film for FCBGA packaging carrier comprises, by weight: 5-10 parts of negatively charged core-shell rubber particles, 15-30 parts of epoxy resin, 50-100 parts of inorganic filler, 10-20 parts of phenoxy resin, 2-5 parts of phenolic resin, 10-45 parts of maleimide, and 10-20 parts of benzoxazine. The invention designs the components of the build-up adhesive film. On the basis of components such as epoxy resin, inorganic filler, phenoxy resin, phenolic resin, etc., no by-products are generated during the curing process of benzoxazine, and the curing shrinkage rate is low. At the same time, a dense nitrogen-containing three-dimensional network structure is generated after curing, so the heat resistance is high, the flame retardancy is good, and the mechanical properties are high. In addition, the phenolic hydroxyl groups in benzoxazine mainly exist in the form of intramolecular hydrogen bonds and intermolecular hydrogen bonds, so the water absorption rate of the build-up adhesive film is low and the dielectric constant is also low; the cured product of maleimide has excellent heat resistance and can reduce the thermal expansion coefficient of the build-up adhesive film; at the same time, the negatively charged core-shell rubber particles can react in the subsequent semi-addition process to improve the bonding force of chemical copper plating, so as to meet the application of the build-up adhesive film in FCBGA packaging carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a process flow diagram of a method for preparing a low-dielectric flame-retardant build-up layer adhesive film for a FCBGA packaging carrier. DETAILED DESCRIPTION
[0033] The present invention provides a low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0035] The existing build-up film has obvious thermal expansion phenomenon, which can easily lead to obvious deformation of the film after curing; at the same time, the dielectric properties are poor, and dielectric loss is easy to occur under the action of alternating electromagnetic fields; and the flame retardant properties of the existing build-up film are poor, as well as poor mechanical properties, and the bonding strength between the film and the copper formed by the semi-additive method needs to be improved.
[0036] Therefore, how to reduce the thermal expansion coefficient of the build-up film, improve the dielectric properties, ensure good flame retardant properties, and at the same time achieve toughening and obtain higher peel strength has become a technical problem that needs to be solved urgently.
[0037] Based on this, the present invention provides a low-dielectric flame-retardant build-up layer adhesive film for FCBGA packaging carrier, which comprises, by weight: 5-10 parts of negatively charged core-shell rubber particles, 15-30 parts of epoxy resin, 50-100 parts of inorganic filler, 10-20 parts of phenoxy resin, 2-5 parts of phenolic resin, 10-45 parts of maleimide, and 10-20 parts of benzoxazine.
[0038] In this embodiment, the negatively charged core-shell rubber particles can react in the subsequent semi-additive process to improve the bonding strength of the chemical copper plating, satisfying the application of the build-up film in the FCBGA package carrier; benzoxazine provides the build-up film with lower water absorption and dielectric constant and higher heat resistance and flame retardancy, and maleimide reduces the thermal expansion coefficient of the build-up film. Therefore, the build-up film obtained by this weight portion can simultaneously achieve toughening and obtain higher peel strength.
[0039] Specifically, due to the presence of negatively charged core-shell rubber particles in the build-up film, the low-dielectric flame-retardant build-up film for FCBGA package carrier can effectively absorb part of the resin slag generated by laser drilling in the subsequent degreasing adjustment process of the semi-additive method, thereby improving the cleaning efficiency of the cleaning agent in the degreasing, ensuring the cleanliness in the hole, and thus improving the binding force of the chemical copper; at the same time, since the negatively charged core-shell rubber particles are locally negatively charged, they can be combined with the locally positively charged main chain in the adjuster in the subsequent degreasing adjustment process. After the adjuster is attached to the surface of the material, it can react with other chemical solutions to produce palladium compounds, which is beneficial to the subsequent formation of activation centers of chemical copper on the surface of the material.
[0040] In some embodiments, the negatively charged core-shell rubber particles are obtained by immersing the core-shell rubber particles in a negatively charged impregnation solution and then subjecting them to a vacuum baking treatment; the immersion conditions are as follows: the immersion temperature is 20-30°C, the relative humidity is 40-60%, and the immersion time is 1-2h; the vacuum baking conditions are as follows: the vacuum baking temperature is 60-80°C, and the vacuum baking time is 1-2h.
[0041] In this embodiment, the core-shell rubber particles can be locally negatively charged by selecting appropriate immersion conditions. If the temperature is too low, the humidity is too high, or the immersion time is too short, the core-shell rubber particles may not be locally charged. If the temperature is too high, the humidity is too low, or the immersion time is too long, the negatively charged core-shell rubber particles will have too much local charge, which may easily cause agglomeration and be unfavorable for processing and use. Post-treatment with a temperature of 60-80°C and vacuum baking for 1-2 hours can fully remove the negatively charged impregnation solution and avoid introducing components in the impregnation solution that affect the performance of the resin system.
[0042] In some embodiments, the negatively charged impregnation solution is obtained by uniformly dispersing 10-15 g of negatively charged components, 0.5-0.8 g of modified graphene oxide, and 1 L of deionized water by ultrasonic dispersion; and the solution can be scaled up in the same proportion.
[0043] In a specific embodiment, the preparation method of the negatively charged component includes the steps of: mixing 2,5-dihydroxyterephthalic acid and N,N-dimethylformamide, adding pentaerythritol and p-toluenesulfonic acid after stirring at 40-50°C, then heating to 153-155°C under nitrogen protection, reacting at normal pressure for 2-3 hours, then turning off the nitrogen, reacting under reduced pressure for 2-3 hours, stopping the reduced pressure, adding undecylenic acid, p-hydroxyanisole and p-toluenesulfonic acid, stirring and reacting at normal pressure at 120-130°C for 2-3 hours to obtain substance A; then mixing substance A, sodium sulfite and sodium nitrate, adding sodium bisulfite solution dropwise while stirring, heating to 105-110°C and stirring for 8-10 hours to obtain the negatively charged component.
[0044] Furthermore, the preparation method of the modified graphene oxide comprises the steps of: dissolving 0.5g of chitosan in 30mL of 1wt% acetic acid solution, adding 25mL of anhydrous ethanol to dilute, stirring evenly, adding 0.17g of p-carboxylbenzaldehyde, stirring and reacting at 60°C for 10h, adding 0.1g of sodium borohydride after the reaction solution is cooled to room temperature, magnetically stirring for 14h, adjusting the pH to neutral with a 1mol / L sodium hydroxide solution, centrifugally collecting the precipitate and washing it with ethanol for 3 times, and drying to obtain phenyl chitosan; adding 0.5g of phenyl chitosan to 15mL of 5wt% acetic acid solution, ultrasonically dispersing, adding 40mL of graphene oxide aqueous solution, stirring and mixing for 16h, centrifuging, precipitating, washing and drying to obtain modified graphene oxide.
[0045] In some embodiments, the maleimide is selected from one or more of phenol-containing bismaleimide, diphenylmethane-type bismaleimide, diaminobenzene-type bismaleimide, diaminodiphenylmethane-type bismaleimide, and polycyclic modified maleimide.
[0046] Among them, bismaleimide has good mechanical properties and dimensional stability, and the product obtained by curing has a dense structure and fewer defects, and has a higher modulus and strength; it also has a benzene ring, an imide heterocycle, and a high degree of crosslinking, so its cured product has excellent heat resistance, and is often used as a high temperature resistant insulating material, etc., and is widely used in the field of electronics. The polycyclic modified maleimide contains very low polarity functional groups such as naphthalene rings, and the low polarity of the naphthyl group can ensure that the maleimide is still stable under the action of an applied electric field, avoiding resonance due to changes in dielectric polarization to increase dielectric loss, and realizing the low dielectric constant and dielectric loss of the layered adhesive film; at the same time, the structure such as the naphthalene ring in the maleimide is composed of multiple benzene rings, and the intermolecular steric hindrance is large, and the bond energy of the chemical bond is larger, and the material is more stable, so the thermal expansion coefficient of the layered adhesive film can be effectively reduced by adding polycyclic modified maleimide.
[0047] In some embodiments, the polycyclic modified maleimide is selected from one or more of polycyclic modified maleimide I, polycyclic modified maleimide II, and polycyclic modified maleimide III;
[0048] Wherein, the structural formula of the polycyclic modified maleimide I is
[0049] The structural formula of the polycyclic modified maleimide II is
[0050] The structural formula of the polycyclic modified maleimide III is
[0051] In some embodiments, the benzoxazine is selected from one or more of bisphenol A type polybenzoxazine, naphthol type polybenzoxazine, unsaturated bond-containing polybenzoxazine, diamine type polybenzoxazine, and DOPO-containing benzoxazine.
[0052] Furthermore, no by-products are generated during the curing process of the benzoxazine, and its curing shrinkage is low. At the same time, a dense nitrogen-containing three-dimensional network structure is generated after curing, so it has high heat resistance, good flame retardancy, and high mechanical properties. In addition, the phenolic hydroxyl groups in the benzoxazine mainly exist in the form of intramolecular hydrogen bonds and intermolecular hydrogen bonds, so its water absorption rate is low and the dielectric constant is also low. Among them, the benzoxazine containing DOPO has a large volume functional group, a low chemical bond polarization rate, can increase the free volume of the polymer, and can effectively improve the dielectric properties of the insulating film; at the same time, DOPO has a hypophosphite structure and high thermal stability. At the same time, the introduction of DOPO (phosphorus) into benzoxazine (nitrogen-containing) can improve the flame retardancy and high temperature resistance of the insulating film through the synergistic effect of nitrogen and phosphorus; in addition, DOPO in benzoxazine belongs to a biphenyl rigid structure, which can effectively increase the energy resistance of the molecular chain segment conformation change, reduce the chain segment diffusion movement under high temperature conditions, thereby reducing the expansion of the molecular chain and achieving a low thermal expansion coefficient.
[0053] In some embodiments, the DOPO-containing benzoxazine is selected from one or more of DOPO-containing benzoxazine I, DOPO-containing benzoxazine II, DOPO-containing benzoxazine III, and DOPO-containing benzoxazine IV;
[0054] Wherein, the structural formula of the DOPO-containing benzoxazine I is
[0055] The structural formula of the DOPO-containing benzoxazine II is
[0056] The structural formula of the DOPO-containing benzoxazine III is
[0057] The structural formula of the DOPO-containing benzoxazine IV is
[0058] In a preferred embodiment, the maleimide is a polycyclic modified maleimide; the benzoxazine is a benzoxazine containing DOPO; the low-dielectric flame-retardant build-up film for the FCBGA package carrier is modified with the aid of components such as polycyclic modified maleimide and benzoxazine containing DOPO, and the polycyclic modified maleimide contains very low polarity functional groups such as naphthalene rings, which can reduce dielectric loss and reduce thermal expansion coefficient; the benzoxazine containing DOPO improves the rigid structure of biphenyl and the single performance and thermal expansion phenomenon, and at the same time improves the flame retardant performance through the synergistic effect of nitrogen and phosphorus; and the negatively charged core-shell rubber particles can react in the subsequent semi-addition process to improve the bonding strength of chemical copper plating, thereby meeting the application of the build-up film in the FCBGA package carrier.
[0059] In some embodiments, the epoxy resin is selected from one or more of bisphenol epoxy resin, biphenyl epoxy resin, phenol epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin, and naphthol phenolic epoxy resin;
[0060] The inorganic filler is selected from one or more of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, and zirconium phosphate;
[0061] The phenolic resin is selected from one or more of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin and dicyclopentadiene phenolic resin.
[0062] In some embodiments, the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier further comprises, by weight: 0.1-0.5 parts of curing accelerator, 3-9 parts of other additives, and 200-300 parts of organic solvent;
[0063] Among them, the curing accelerator is selected from one or more of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, 4-dimethylaminopyridine, and 2-phenylimidazole; the other auxiliary agents are selected from one or more of thickeners, defoamers, leveling agents, leveling agents, adhesion-imparting agents, and colorants; the organic solvent is selected from one or more of toluene, xylene, butanone, methyl ethyl ketone, cyclohexanone, ethyl acetate, and N,N-methylformamide.
[0064] In some embodiments, the thickness of the low-dielectric flame-retardant build-up layer adhesive film for the FCBGA package carrier is 10-100 μm.
[0065] In addition, Figure 1 As shown, the present invention also provides a method for preparing a low-dielectric flame-retardant build-up layer adhesive film for a FCBGA package carrier, comprising the steps of:
[0066] Step S10: providing a substrate;
[0067] Step S20: After mixing the components of the low-K flame retardant build-up layer adhesive film for FCBGA package carrier in parts by weight, coating the mixture on the substrate, and drying the mixture to obtain the low-K flame retardant build-up layer adhesive film for FCBGA package carrier.
[0068] In this embodiment, after the components of the low-dielectric flame retardant build-up layer adhesive film for FCBGA package carrier are uniformly mixed according to mass proportions, the low-dielectric flame retardant build-up layer adhesive film for FCBGA package carrier can be prepared by coating; the preparation method is simple, and the prepared low-dielectric flame retardant build-up layer adhesive film for FCBGA package carrier has low dielectric loss and low thermal expansion coefficient, and has high flame retardant performance, and can also improve the bonding strength of chemical copper plating in the subsequent semi-additive process.
[0069] In some embodiments, the thickness of the substrate is 10-150 μm; for example, the thickness of the substrate can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, etc.
[0070] In a preferred embodiment, the thickness of the substrate is 25-50 μm.
[0071] It should be noted that the present invention has no special limitation on the selection of substrates, and any substrate commonly used in the art can be used, including but not limited to: PET release film, polyethylene film, polypropylene film or polyvinyl chloride film. In order to facilitate the subsequent removal of the substrate, preferably, the polyethylene film, polypropylene film or polyvinyl chloride film can be corona treated in advance before use.
[0072] In some embodiments, in step S20, the drying temperature is 80-130°C; for example, the drying temperature may be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 120°C, 125°C or 130°C, etc.
[0073] In some embodiments, in step S20, the drying time is 3-10 min; for example, the drying time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc.
[0074] In some embodiments, the step S20 further includes a post-processing step after drying; the post-processing method is to remove the substrate to obtain a build-up adhesive film without substrate adhesion.
[0075] In addition, the present invention also provides an application of a build-up adhesive film in a FCBGA package carrier.
[0076] In some embodiments, a semi-additive method is required to obtain a FCBGA package carrier by using the build-up film, and the specific processing includes the following steps:
[0077] Step S100: vacuum pressing the build-up adhesive film and the inner substrate to form a substrate A with a build-up adhesive film by a vacuum molding machine;
[0078] Specifically, the inner layer substrate is selected from any one of a BT resin substrate, an epoxy glass substrate, a polyester substrate, a polyimide substrate, a glass substrate, and a metal substrate; the vacuum laminator is selected from any one of a vacuum pressurized laminator manufactured by Meiki Manufacturing Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and an intermittent vacuum pressurized laminator; the heating and pressing temperature of the vacuum pressing molding is 60-160°C, the heating and pressing pressure of the vacuum pressing molding is 0.098-1.77MPa, and the heating and pressing time of the vacuum pressing molding is 20-400s; and the pressing is preferably carried out under reduced pressure conditions with a pressure below 26.7hPa.
[0079] In a preferred embodiment, the heating and pressing temperature of the vacuum pressing molding is 80-140° C., the heating and pressing pressure of the vacuum pressing molding is 0.29-1.47 MPa, and the heating and pressing time of the vacuum pressing molding is 30-300 s.
[0080] Step S200: thermally curing the substrate A with the build-up adhesive film so that the build-up adhesive film is cured into an insulating layer, thereby obtaining a substrate B with an insulating layer;
[0081] Specifically, the curing temperature of the build-up adhesive film is 120-240° C., and the curing time is 5-120 min. Before the build-up adhesive film is thermally cured, the build-up adhesive film can be pre-cured, and the pre-curing temperature is 50-120° C. and the pre-curing time is 5-150 min.
[0082] In a preferred embodiment, the curing temperature of the build-up adhesive film is 150-220° C., and the curing time is 10-100 min; the pre-curing temperature is 60-115° C., and the pre-curing time is 15-120 min.
[0083] Furthermore, the curing temperature of the build-up adhesive film is 170-210° C., and the curing time is 15-100 min; the pre-curing temperature is 70-110° C., and the pre-curing time is 15-100 min.
[0084] Step S300: drilling holes in the substrate B with the insulating layer to obtain a substrate C with holes;
[0085] Specifically, the drilling method can be selected from one of mechanical drilling, laser drilling, plasma drilling, or a combination of at least two of them; and the size and shape of the holes obtained by drilling can be appropriately determined according to the design of the FCBGA package carrier, and the types of holes include through holes, blind holes, etc.
[0086] Step S400: roughening the insulating layer of the substrate C with holes to obtain a roughened substrate D;
[0087] Specifically, the steps and conditions of the roughening treatment are not particularly limited, and the steps and conditions commonly used in forming the insulating layer of the package carrier can be adopted. For example, the insulating layer can be roughened by sequentially performing a fluffing treatment using a fluffing liquid, an oxidizing treatment using an oxidant, and a reducing treatment using a neutralizing liquid. Preferably, the fluffing liquid is selected from "Swelling Dip Securiganth P", "Swelling Dip Securiganth SBU" and the like of ATOTECH, and the fluffing conditions are immersion in the fluffing liquid at 30-90°C for 1-20 minutes; preferably, the oxidant is selected from alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securiganth P" of ATOTECH, and the oxidizing conditions are immersion in the oxidant solution at 60-100°C for 10-30 minutes; preferably, the neutralizing liquid is selected from "Reduction Solution Securiganth P" of ATOTECH, and the neutralizing conditions are immersion in the neutralizing liquid at 30-80°C for 5-30 minutes.
[0088] Step S500: forming a conductor layer on the insulating layer of the roughened substrate D to obtain a substrate E with a conductor layer;
[0089] Specifically, the substrate D is sequentially subjected to the steps of degreasing adjustment (Cleaner), micro-etching cleaning (Etch Cleaner), pre-dipping (Pre Dip), activation (Activator), reduction (Reducer), chemical copper (E-less copper), pattern transfer, hole filling under pattern electroplating, film removal, flash etching, etc., to obtain a substrate E with a conductor layer.
[0090] Step S600: Repeat steps S100 to S500 for substrate E as required to obtain a FCBGA package carrier, wherein the number of layers of the package carrier is selected from 4 to 20.
[0091] Specifically, when the maleimide is a polycyclic modified maleimide; and the benzoxazine is a benzoxazine containing DOPO, the present invention has the following beneficial effects:
[0092] 1. Negatively charged core-shell rubber particles are obtained by modification. In the subsequent semi-additive process, the adsorption effect generated by the negative charge is used to improve the cleanliness of the drill hole in the adjustment process, and at the same time, the activation center of the chemical copper is formed, thereby improving the degree of chemical copper stripping.
[0093] 2. By using polycyclic modified maleimide containing very low polar functional groups such as naphthalene rings, it is possible to ensure that maleimide remains stable under the action of an external electric field, avoid resonance due to changes in dielectric polarization, and thus increase dielectric loss, thereby achieving a low dielectric constant and dielectric loss of the build-up film; and by utilizing the naphthalene ring structure with large steric hindrance, the thermal stability of the material can be improved, effectively reducing the thermal expansion coefficient of the build-up film.
[0094] 3. By using the large functional groups of benzoxazine containing DOPO, the free volume of the polymer is increased, which can effectively improve the dielectric properties of the insulating film; at the same time, since DOPO belongs to a rigid structure of phenyl chains, it can effectively increase the energy resistance of the conformational change of the molecular chain segments, thereby reducing the movement of the molecular chain and achieving a low thermal expansion coefficient.
[0095] 4. The hypophosphite structure of DOPO in benzoxazine has high thermal stability. At the same time, the introduction of DOPO (containing phosphorus) into benzoxazine (containing nitrogen) can promote the formation of a cross-linked network with the polymer chain through the synergistic effect of nitrogen and phosphorus, thereby improving the flame retardant properties of the insulating film.
[0096] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.
[0097] The sources of some components in the embodiments and comparative examples are as follows:
[0098] Negatively charged core-shell rubber particles I: A negatively charged impregnation solution was prepared according to the composition and preparation method of the negatively charged impregnation solution, and core-shell rubber particles "AC3816N" of AICA Industries, Japan were immersed in the negatively charged impregnation solution under the conditions of temperature 25°C, relative humidity 50%, and immersion time 1.5h; post-treatment conditions were temperature 70°C, vacuum baking for 1.5h, to obtain negatively charged core-shell rubber particles I;
[0099] Negatively charged core-shell rubber particles II: A negatively charged impregnation solution was prepared according to the composition and preparation method of the negatively charged impregnation solution, and the core-shell rubber particles "XER-91" of Japan Synthetic Rubber Co., Ltd. were immersed in the negatively charged impregnation solution. The immersion conditions were temperature 30°C, relative humidity 55%, and immersion time 1 hour. The post-treatment conditions were temperature 75°C and vacuum baking for 2 hours to obtain negatively charged core-shell rubber particles II.
[0100] Epoxy resin: bisphenol A type epoxy resin (“jER828EL” from Mitsubishi Chemical Corporation of Japan), biphenyl type epoxy resin (“NC3000L” from Nippon Kayaku Co., Ltd.), glycidylamine type epoxy resin (“630” from Mitsubishi Chemical Corporation of Japan), and dicyclopentadiene type epoxy resin (“HP-7200H” from DIC Corporation).
[0101] Inorganic filler: silicon dioxide ("SOC2" from Yaduma Co., Ltd., Japan), silicon dioxide ("DQ1028L" from Jiangsu Lianrui Co., Ltd.).
[0102] Phenoxy resin: “YX7200B35” from Mitsubishi Chemical Corporation, Japan.
[0103] Phenolic resin: DIC "KA-1160", Meiwa Chemical Co., Ltd. "MEH-7851".
[0104] Maleimide: Designer Molecules "BMI-689", Nippon Kayaku Co., Ltd. "MIR-3000-70MT".
[0105] Benzoxazine: JFE Chemical Company "JBZ-OD100".
[0106] Example 1
[0107] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0108] 10 parts of negatively charged core-shell rubber particles I, 6 parts of bisphenol A type epoxy resin (jER828EL), 5 parts of biphenyl type epoxy resin (NC3000L), 4 parts of glycidylamine type epoxy resin (630), 100 parts of silica (SOC2), 20 parts of phenoxy resin (YX7200B35), 5 parts of phenolic resin (KA-1160), 10 parts of maleimide (BMI-689), 20 parts of benzoxazine III containing DOPO, 0.1 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0109] The preparation method of the above-mentioned build-up film is as follows:
[0110] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 80° C. for 10 min, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 100 μm.
[0111] Example 2
[0112] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0113] 10 parts of negatively charged core-shell rubber particles I, 6 parts of bisphenol A type epoxy resin (jER828EL), 5 parts of biphenyl type epoxy resin (NC3000L), 4 parts of glycidylamine type epoxy resin (630), 100 parts of silica (SOC2), 20 parts of phenoxy resin (YX7200B35), 5 parts of phenolic resin (KA-1160), 10 parts of polycyclic modified maleimide I, 20 parts of benzoxazine (JBZ-OD100), 0.1 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0114] The preparation method of the above-mentioned build-up film is as follows:
[0115] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 130° C. for 3 minutes, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 10 μm.
[0116] Example 3
[0117] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0118] 10 parts of negatively charged core-shell rubber particles I, 6 parts of bisphenol A type epoxy resin (jER828EL), 5 parts of biphenyl type epoxy resin (NC3000L), 4 parts of glycidylamine type epoxy resin (630), 100 parts of silica (SOC2), 20 parts of phenoxy resin (YX7200B35), 5 parts of phenolic resin (KA-1160), 10 parts of polycyclic modified maleimide I, 20 parts of benzoxazine III containing DOPO, 0.1 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0119] The preparation method of the above-mentioned build-up film is as follows:
[0120] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 110° C. for 5 minutes, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 40 μm.
[0121] Example 4
[0122] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0123] 5 parts of negatively charged core-shell rubber particles II, 30 parts of dicyclopentadiene epoxy resin (HP-7200H), 50 parts of silica (DQ1028L), 10 parts of phenoxy resin (YX7200B35), 2 parts of phenolic resin (MEH-7851), 45 parts of maleimide (MIR-3000-70MT), 10 parts of benzoxazine I containing DOPO, 0.5 parts of 2-phenylimidazole (2PZ) and 200 parts of butanone.
[0124] The preparation method of the above-mentioned build-up film is as follows:
[0125] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 80° C. for 10 min, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 40 μm.
[0126] Example 5
[0127] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0128] 5 parts of negatively charged core-shell rubber particles II, 30 parts of dicyclopentadiene epoxy resin (HP-7200H), 50 parts of silica (DQ1028L), 10 parts of phenoxy resin (YX7200B35), 2 parts of phenolic resin (MEH-7851), 45 parts of polycyclic modified maleimide II, 10 parts of benzoxazine (JBZ-OD100), 0.5 parts of 2-phenylimidazole (2PZ) and 200 parts of butanone.
[0129] The preparation method of the above-mentioned build-up film is as follows:
[0130] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 130° C. for 3 minutes, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 40 μm.
[0131] Example 6
[0132] This embodiment provides a low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier and a preparation method thereof. The build-up adhesive film includes the following components in parts by weight:
[0133] 5 parts of negatively charged core-shell rubber particles II, 30 parts of dicyclopentadiene epoxy resin (HP-7200H), 50 parts of silica (DQ1028L), 10 parts of phenoxy resin (YX7200B35), 2 parts of phenolic resin (MEH-7851), 45 parts of polycyclic modified maleimide II, 10 parts of benzoxazine I containing DOPO, 0.5 parts of 2-phenylimidazole (2PZ) and 200 parts of butanone.
[0134] The preparation method of the above-mentioned build-up film is as follows:
[0135] The components of the build-up adhesive film were mixed uniformly, coated on a PET release film, dried at 80° C. for 10 min, and then the PET release film was removed to obtain a build-up adhesive film with a thickness of 40 μm.
[0136] Comparative Example 1
[0137] This comparative example provides a build-up film and a preparation method thereof, which differs from Example 1 only in that the build-up film does not add 20 parts of benzoxazine III containing DOPO, and 10 parts of negatively charged core-shell rubber particles I are replaced with 10 parts of core-shell rubber particles (AC3816N), and other conditions are the same as Example 1.
[0138] Comparative Example 2
[0139] This comparative example provides a build-up adhesive film and a preparation method thereof, which differs from Example 4 only in that the build-up adhesive film does not contain 10 parts of phenoxy resin (YX7200B35) and 10 parts of benzoxazine I containing DOPO, and 5 parts of negatively charged core-shell rubber particles II are replaced with 5 parts of core-shell rubber particles (XER-91), and other conditions are the same as Example 4.
[0140] The performance of the build-up adhesive films provided in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0141] Thermal expansion coefficient: The build-up adhesive with PET release film provided in the above-mentioned embodiments and comparative examples was cured at 180°C for 60 min, and then the release film was peeled off to obtain a pre-cured build-up adhesive film; the pre-cured build-up adhesive film was cut into test pieces with a width of about 6 mm and a length of about 15 mm, and a thermal mechanical analysis was performed using a thermomechanical analysis device (Mettler Toledo "TMA SDTA2+") under the conditions of a preload force of 0.02 N, a heating range of 25°C to 260°C, and a heating rate of 10°C / min to obtain the thermal expansion coefficient in the range of 25°C to 150°C (CTEx-y, 25~150°C).
[0142] Flame retardancy: The build-up adhesive film with PET release film provided in the above embodiments and comparative examples was pressed with the substrate by a film laminating machine, and the build-up adhesive film (the side without release film) was pressed on both sides of the substrate to obtain a laminate; after the lamination was completed, the release film on the laminate was removed, and the resin composition layer was thermally cured (at 190°C for 90 minutes) to form a cured product on both sides of the substrate. The laminate (thickness of about 380 μm) was cut into 12.7 mm × 127 mm size with an edge of 1.27 mm, and tested according to the UL-94V standard, and the test results were recorded.
[0143] Dielectric constant and dielectric loss tangent: The build-up adhesive with PET release film provided in the above-mentioned embodiments and comparative examples is cured at 180°C for 30 minutes, and then the release film is peeled off to obtain a pre-cured build-up adhesive film; the pre-cured build-up adhesive film is cut into 2mm×80mm test pieces (3 pieces), and then the dielectric constant and dielectric loss tangent of each test piece are measured using the "HP8362B" of Agilent Technologies Inc. by using the cavity resonance perturbation method at a measurement frequency of 5.8GHz and a measurement temperature of 23°C, and the average values of the dielectric constant and dielectric loss tangent of the three test pieces are calculated as the dielectric constant and dielectric loss tangent.
[0144] Copper peel strength: The roughened substrate D in step (4) was subjected to degreasing adjustment, microetching cleaning, prepreg, activation, reduction, chemical copper, water washing and baking, pickling, chemical electroplating and other processes in sequence, and then baked at 150° C. for 120 min to obtain an evaluation substrate; an anti-peel strength tester (Guangdong Dinglu "RAY-BL01") was used to evaluate the copper foil peel strength of the substrate, a rectangular cut with a width of 10 mm and a length of 100 mm was cut on the copper layer, one end of the rectangular copper layer was peeled off and clamped with the clamp of the anti-peel strength tester, and the aforementioned rectangular part was peeled off in the vertical direction at a rate of 500 mm / min, and the corresponding load (N / cm) was recorded.
[0145] Finally, the measured data of thermal expansion coefficient, flame retardancy, dielectric constant, dielectric loss tangent and copper peel strength are shown in Table 1.
[0146]
[0147] In summary, the present invention provides a low-dielectric flame-retardant build-up layer adhesive film for FCBGA packaging carrier and a preparation method thereof. The low-dielectric flame-retardant build-up layer adhesive film for FCBGA packaging carrier comprises, by weight: 5-10 parts of negatively charged core-shell rubber particles, 15-30 parts of epoxy resin, 50-100 parts of inorganic filler, 10-20 parts of phenoxy resin, 2-5 parts of phenolic resin, 10-45 parts of maleimide, and 10-20 parts of benzoxazine. The invention designs the components of the build-up adhesive film. On the basis of components such as epoxy resin, inorganic filler, phenoxy resin, phenolic resin, etc., no by-products are generated during the curing process of benzoxazine, and the curing shrinkage rate is low. At the same time, a dense nitrogen-containing three-dimensional network structure is generated after curing, so the heat resistance is high, the flame retardancy is good, and the mechanical properties are high. In addition, the phenolic hydroxyl groups in benzoxazine mainly exist in the form of intramolecular hydrogen bonds and intermolecular hydrogen bonds, so the water absorption rate of the build-up adhesive film is low and the dielectric constant is also low; the cured product of maleimide has excellent heat resistance and can reduce the thermal expansion coefficient of the build-up adhesive film; at the same time, the negatively charged core-shell rubber particles can react in the subsequent semi-addition process to improve the bonding force of chemical copper plating, so as to meet the application of the build-up adhesive film in FCBGA packaging carriers.
[0148] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier, characterized in that: The composition comprises, by weight: 5-10 parts of negatively charged core-shell rubber particles, 15-30 parts of epoxy resin, 50-100 parts of inorganic filler, 10-20 parts of phenoxy resin, 2-5 parts of phenolic resin, 10-45 parts of maleimide and 10-20 parts of benzoxazine; The negatively charged core-shell rubber particles are obtained by immersing the core-shell rubber particles in a negatively charged impregnation solution and then performing a vacuum baking treatment; the immersion conditions are as follows: the immersion temperature is 20-30° C., the relative humidity is 40-60%, and the immersion time is 1-2 hours; the vacuum baking conditions are as follows: the vacuum baking temperature is 60-80° C., and the vacuum baking time is 1-2 hours; the negatively charged impregnation solution is composed of a negatively charged component, modified graphene oxide, and deionized water in a mass ratio of (10-15):(0.5-0.8):1000; The preparation method of the negatively charged component comprises the steps of: mixing 2,5-dihydroxyterephthalic acid and N,N-dimethylformamide, adding pentaerythritol and p-toluenesulfonic acid after stirring at 40-50°C, then heating to 153-155°C under nitrogen protection, reacting at normal pressure for 2-3h, then turning off the nitrogen, reacting at reduced pressure for 2-3h and stopping the reduced pressure, adding undecylenic acid, p-hydroxyanisole and p-toluenesulfonic acid, stirring and reacting at normal pressure for 2-3h at 120-130°C to obtain substance A; then mixing substance A, sodium sulfite and sodium nitrate, dropping sodium bisulfite solution, heating to 105-110°C, stirring and reacting for 8-10h to obtain the negatively charged component; The maleimide is selected from one or more of phenol-containing bismaleimide, diphenylmethane bismaleimide, diaminobenzene bismaleimide, diaminodiphenylmethane bismaleimide, and polycyclic modified maleimide; the polycyclic modified maleimide is selected from one or more of polycyclic modified maleimide I, polycyclic modified maleimide II, and polycyclic modified maleimide III; Wherein, the structural formula of the polycyclic modified maleimide I is ; The structural formula of the polycyclic modified maleimide II is ; The structural formula of the polycyclic modified maleimide III is ; The benzoxazine is selected from one or more of bisphenol A type polybenzoxazine, naphthol type polybenzoxazine, unsaturated bond-containing polybenzoxazine, diamine type polybenzoxazine, and DOPO-containing benzoxazine; The low-dielectric flame-retardant build-up adhesive film for the FCBGA package carrier includes polycyclic modified maleimide and / or benzoxazine containing DOPO.
2. The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier according to claim 1, characterized in that: The DOPO-containing benzoxazine is selected from one or more of DOPO-containing benzoxazine I, DOPO-containing benzoxazine II, DOPO-containing benzoxazine III, and DOPO-containing benzoxazine IV; Wherein, the structural formula of the DOPO-containing benzoxazine I is ; The structural formula of the DOPO-containing benzoxazine II is ; The structural formula of the DOPO-containing benzoxazine III is ; The structural formula of the DOPO-containing benzoxazine IV is .
3. The low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier according to claim 1, characterized in that: The epoxy resin is selected from one or more of bisphenol epoxy resin, biphenyl epoxy resin, phenol epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, and aralkyl phenolic epoxy resin; The inorganic filler is selected from one or more of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, and zirconium phosphate; The phenolic resin is selected from one or more of bisphenol A phenolic resin, phenolic resin, biphenyl phenolic resin and dicyclopentadiene phenolic resin.
4. The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier according to claim 1, characterized in that: The low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier board further comprises, by weight: 0.1-0.5 parts of curing accelerator, 3-9 parts of other auxiliary agents, and 200-300 parts of organic solvent; Wherein, the curing accelerator is selected from one or more of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, 4-dimethylaminopyridine, and 2-phenylimidazole; The other auxiliary agents are selected from one or more of thickeners, defoamers, leveling agents, leveling agents, adhesion-imparting agents, and colorants; The organic solvent is selected from toluene, xylene, butanone, methyl ethyl ketone, cyclohexanone, ethyl acetate, N,N -methylformamide or more.
5. The low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier according to claim 1, characterized in that: The thickness of the low-dielectric flame-retardant build-up layer adhesive film for the FCBGA package carrier is 10-100 μm.
6. A method for preparing a low-dielectric flame-retardant build-up layer adhesive film for FCBGA package carrier according to any one of claims 1 to 5, characterized in that: Includes steps: Providing a substrate; The components of the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier are mixed in parts by weight, coated on the substrate, and dried to obtain the low-dielectric flame-retardant build-up adhesive film for FCBGA package carrier.
Citation Information
Patent Citations
Method for assembling polyelectrolyte / inorganic nano-particle multilayer films on surfaces of wood materials layer by layer
CN103736634A
Silicon / graphene composite thin film electrode and preparation method thereof and lithium ion battery
CN107871850A